Limited Conflicts Under the Nuclear Umbrella Indian and Pakistani Lessons from the Kargil Crisis - Tellis, Ashley J. (RAND Corporation, 2001)
This report examines the views of India and Pakistan on the significance ofPakistan_s foray into the Kargil-Dras sector in a limited war that has cometo be known as the Kargil conflict. The goal of the analysis is to assessboth combatants_ perceptions of the crisis, with a view to evaluating thepossibilities of future Kargil-like events and the implications of thelessons each country learned for stability in South Asia. The analysis isbased almost exclusively on Indian and Pakistani source materials.The Kargil crisis demonstrated that even the presence of nuclear weaponsmight not appreciably dampen security competition between the region_slargest states. However, the question remains of whether or not the Kargilwar represents a foretaste of future episodes of attempted nuclear coercionif India and Pakistan believe that their nuclear capabilities provide themthe immunity required to prosecute a range of military operations short ofall-out war.